Superactivity induced by micellar systems as the key for boosting the yield of enzymatic reactions - Sintra, Tânia E.; Ventura, Sónia P.M.; Coutinho, João A.P. (Journal of molecular catalysis. B, Enzymatic, 2014)
•Superactivity is the increase on the enzymatic activity promoted by microemulsion formation.•Microemulsions inducing superactivity are formed by surfactants or surface active ILs.•Superactivation of various enzymes, in diverse reactions and by various surfactants is analyzed.•The ILs tunability is the vehicle toward new methodologies promoting the enzyme activation.•A multidisciplinary study is needed to understand the phenomenon and its industrial application. The superactivity phenomenon is a concept that expresses a significant increase on the enzymatic activity by common surfactants or ionic liquids emulsions. In this context, this work presents an overview of the literature on this subject, focused on the type, and characteristics of the surfactants and ILs reported in literature as superactivity inductors and the enzymes and reactions hitherto investigated in the superactivity context. It intends to emphasize the necessity of a multidisciplinary approach to this subject bringing together scientific communities of different fields to foster the understanding of this phenomenon, and to identify the type of reactions and processes that could and should be improved by it, having into account its potential application at industrial level.